2021
DOI: 10.1021/acs.energyfuels.1c01424
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Morphology Effect of Ceria on the Catalytic Performance of NiO–PdO/CeO2 Nanoparticles for Thermo-oxidation of n-C7 Asphaltenes under Isothermal Heating at Different Pressures

Abstract: The overall objective of this study is to evaluate the effect of morphologies (C, cubic; O, orthorhombic; and S, spherical) of ceria in the catalytic activity for n-C7 asphaltene thermo-oxidation. In this way, cubic (C-CeO2), orthorhombic (O-CeO2), and spherical (S-CeO2) ceria nanoparticles were synthesized using the hydrothermal method and doped with 1.0% in a mass fraction of Ni and Pd oxides by incipient wetness impregnation. The catalytic activity of the systems was evaluated through non-isothermal and iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…These results agree with literature reports for the adsorption of different asphaltene types onto different solid surfaces [36,37,42,43,73]. The adsorption isotherms follow a type Ib behavior according to the IUPAC classification [87], indicating that there is a strong affinity between the n-C 7 asphaltenes and the synthesized materials [31,90]. On another side, considering the acidic character of tungsten oxide, this behavior suggests the basicity of the asphaltenes in addition the presence of heteroatoms such as nitrogen and oxygen in the asphaltene molecules, which favor the interaction with the nanoparticle surface [91,92].…”
Section: Asphaltene Adsorption Isotherms Effect Of Synthesis Conditionssupporting
confidence: 91%
See 1 more Smart Citation
“…These results agree with literature reports for the adsorption of different asphaltene types onto different solid surfaces [36,37,42,43,73]. The adsorption isotherms follow a type Ib behavior according to the IUPAC classification [87], indicating that there is a strong affinity between the n-C 7 asphaltenes and the synthesized materials [31,90]. On another side, considering the acidic character of tungsten oxide, this behavior suggests the basicity of the asphaltenes in addition the presence of heteroatoms such as nitrogen and oxygen in the asphaltene molecules, which favor the interaction with the nanoparticle surface [91,92].…”
Section: Asphaltene Adsorption Isotherms Effect Of Synthesis Conditionssupporting
confidence: 91%
“…During this process, different reactions occur simultaneously, generating physicochemical changes in the heavy oil, even leading to upgrading through viscosity reduction and API gravity increase. Nevertheless, the conversion of heavy and refractory fractions such as asphaltenes into lighter compounds struggles to occur behind the combustion zone, as the decomposition temperature could be higher than 400 • C [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…This was primarily because the PAHs tended to adsorb on the surface of the nanoparticles. Mazloom et al reported that PAH structures with higher aromaticity and polarity tended to adsorb more readily onto the surface of nanoparticles. The influence of the geometry of the nanocomposites (cubic, orthorhombic, and spherical) on the thermo-oxidate process has also been evaluated; Medina et al demonstrated that the conversion rates of PAHS were highest for cubic cerium nanoparticles, followed by orthorhombic and spherical nanoparticles. Despite the valuable contributions of these studies, they do not consider the effect of the structural and compositional characteristics of PAHs on the thermal-oxidative process.…”
Section: Introductionmentioning
confidence: 99%
“…One potential solution is the transformation of these PAHs into a less hazardous or nonhazardous compound by catalytic procedures, ,, with thermal-oxidative processes being a highly promising solution . Thermogravimetric analysis is one of the most commonly used techniques for studying the thermo-oxidation process of PAHs. , It allows researchers to obtain thermo-oxidation profiles that can be used to evaluate the impact of different catalysts used during the process, including nanotechnology. Nassar et al evaluated three species of metal oxide nanoparticles and found that the activation energy required to oxidize PAHs was reduced, leading to more favorable reaction pathways and oxidation kinetics. This was primarily because the PAHs tended to adsorb on the surface of the nanoparticles. Mazloom et al reported that PAH structures with higher aromaticity and polarity tended to adsorb more readily onto the surface of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…These authors demonstrated the combination of ultrahigh-resolution FT-ICR and cyclic ion mobility mass spectrometry as an effective tool to overcome the limitation on structural determination of asphaltene molecules to shed important insights into hydrotreating mechanisms. The article of Medina, Cortés, Franco, and co-workers reports the effect of morphologies of ceria nanoparticles on the catalytic conversion of asphaltenes using multiple complementary characterizations. Friederici, Rüger, and co-workers from the University of Rostock reported the characterization of plastic pyrolysis chars using thermal analysis hyphenated with mass spectrometric approaches.…”
Section: Characterization Of Processing Productsmentioning
confidence: 99%